2019
DOI: 10.3390/nu12010012
|View full text |Cite
|
Sign up to set email alerts
|

Age-Appropriate Feeding Practices in Cambodia and the Possible Influence on the Growth of the Children: A Longitudinal Study

Abstract: Age-appropriate feeding practice (ADF) during early childhood are vital for optimal nutrition. This longitudinal study determined the effect of selected risk factors and ADF, as described by the National Nutritional Recommendations, on linear and ponderal growth of children below 24 months of age. Weight and length measures were used to calculate z-scores of anthropometric measures by WHO standards. The prevalence of stunting increased from 13.2% to 32.4% over time, while prevalence of wasting remained stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
2
17
0
2
Order By: Relevance
“…A recent community-based intervention which included oral health education and fluoride varnish by non-dental health workers in rural Cambodia led to a lower ECC prevalence in children aged two years [ 43 ]. Regarding nutritional interventions, adaptation of age-appropriating feeding practices from an early age has contributed to improving child growth and development in Cambodia [ 44 ]. This integrated approach could help to reduce the incidence of both ECC and underweight among young rural children.…”
Section: Discussionmentioning
confidence: 99%
“…A recent community-based intervention which included oral health education and fluoride varnish by non-dental health workers in rural Cambodia led to a lower ECC prevalence in children aged two years [ 43 ]. Regarding nutritional interventions, adaptation of age-appropriating feeding practices from an early age has contributed to improving child growth and development in Cambodia [ 44 ]. This integrated approach could help to reduce the incidence of both ECC and underweight among young rural children.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four-hour recall information was used for the construction of related indicators, namely, type of breastfeeding, frequency of feedings (breast milk and complementary foods), and quantity of food consumed [23]. Feeding practices were considered for the following age groups: (I) 0–5.99 months, (II) 6–8.99 months, (III) 9–11.99 months, (IV) 12–23.99 months, and (IV) 24 months+ [24]. Appropriateness of feeding practices was measured at each follow-up round through a binary value of appropriate (0) or not appropriate (1) and further used in the analysis as: Appropriate at all times (0), Sometimes appropriate (1), or Not appropriate (2).…”
Section: Methodsmentioning
confidence: 99%
“…Mothers who can increase their capacity in childcare based on the child's age can assure that their child's nutritional consumption will be fulfilled. The practice of feeding children based on 4 indicators of child feeding globally was not taken seriously in this study by caregivers (15) . The same study also reported from Guatemala, 2014 that the indicators of the quality of child feeding always differ between regions.…”
Section: Discussionmentioning
confidence: 99%